Research on the Advance Role of Institutional Quality on Achieving Environmental Efficiency in Sub Sahara Africa - Bahizire, Grace Mulindwa; Fanglin, Li; Appiah, Michael; Xicang, Zhao (Frontiers in Environmental Science, 2022)
The study investigates the impact of institutional quality on environmental efficiency in the presence of the Environmental Kuznets Curve (EKC) using data on desirable and undesirable outputs as well as institutional quality dimensions from the World Governance Indicators (WGI) for 19 Sub-Sahara African (SSA) countries over an annual period from 2005 to 2014. Environmental efficiency was low in eight SSA countries and excellent in eleven others, according to the efficiency results. Two countries had the highest average environmental efficiency over the first period, while one had the lowest. In 2013, the majority of SSA countries had high efficiency indexes, with one country having an index of 2.098 and four countries having efficiency rates of one. After controlling for industrialization, energy consumption, and population variables, the results show that corruption control and regulatory quality lower environmental efficiency while government effectiveness increases. The DH causality test revealed that environmental efficiency, control of corruption, regulatory quality, energy consumption, and population had no causal relationship. There are also one-way causal linkages between environmental efficiency and government effectiveness and industrialization.